ผลของไนโตรเจนและฟอสฟอรัสต่อการเติบโตและองค์ประกอบทางชีวเคมีของสาหร่ายทะเล สกุล Caulerpa, Ulva และ Gracilaria - เอกธิดา ทองเด็จ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The effects of nitrogen and phosphorus on growth and biochemical composition of marine macroalgae species Caulerpa lentilifera, Ulva rigida and Gracilaria fisheri were investigated. The highest growth rate of C. lentilifera, U. rigida and G. fisheri were found in the medium with N:P ratio 10:1, 30:1 and 12:1, respectively. The green algae C. lentilifera showed preference of nitrogen in form of NO₃ over NH₄⁺ since its growth rate was maximized in the NO₃:NH₄⁺ ratio of 96:4. Another green algae, U. rigida and a red algae G. fisheri exhibited better growth in medium with high NH₄⁺ (NO₃:NH₄⁺ ratio of 0:100). These algae also showed different requirement for nutrient concentrations with the highest requirement of C. lentilifera; 1850 μM of DIN and 151 μM of DIP and 750 μM of DIN and 26 μM of DIP for U. rigida and 50 μM of DIN and 8 μM of DIP for G. fisheri. This discrepancy may due to algal experience in different nutrient status in their environments. The N:P ratio and the DIN and DIP concentrations have significant effects on biochemical compositions of these macroalgae. The highest amounts of carbohydrate and the amounts of protein in algae were found in high N:P ratio and high DIN and DIP concentrations while there is no significant effects on the amounts of ash, the amounts of lipid and fatty acid profile. The most abundant fatty acids found in these algae comprised of Palmitic Acid (16:0) and Oleic Acid (C18:1). The form of nitrogen, nitrate or ammonium, has no significant effect on the amounts of ash, the amounts of protein, the amounts of carbohydrate and the amounts of lipid in C.lentilifera and U. rigida. However, there is a tendency of higher amounts of protein, carbohydrate and lipid under higher ammonium condition. On the other hand, the amounts of carbohydrates in the red algae G. fisheri increased significantly with the increase in nitrate concentration rather than ammonium concentration. Chlorophyta species C. lentilifera and U. rigida can be the bioindicator for eutrophic environment. They have the potential to treat high nitrogen wastewater especially wastewater from coastal aquaculture because of the luxury ammonium uptake. In addition, they have the potential as raw materials for biodiesel because of their high Palmitic acid contents. Due to high biochemical composition especially the protein contents, a green alga U. rigida can be used as the potential food source for aquaculture feed. A rhodophyta species G. fisheri has high ability to uptake ammonium, so it is useful for coastal wastewater treatment as well. This macroalga is also suitable for using as health food because of its high Oleic acid contents.